Empowering Malaysian women entrepreneurs: analyzing the role of socio-cultural factors and support systems in emerging markets - Sapiai, Nur Shaliza; Mohd Ishak @ Zainudin, Fadhilah; Abdul Rahman, Khadijah; Mat Nawi, Hafizah; Baker, Rogis (Faculty of Information Management, 2025)
This paper provides a review of the literature on the integral role of socio-cultural factors and support systems that can enable success for women entrepreneurs in emerging markets. It also emphasizes different barriers that women face because of socio-cultural attitudes and the importance of family and community influences. The study also delves into the role of governmental policies and NGO support in shaping the small business landscape, highlighting its influence on access to funding and training programs. Comparative studies concerning several other countries such as Malaysia, Indonesia, and Bangladesh reveal that varied cultural contexts are important for accessing women’s entrepreneurship. Among continuing challenges, such as financial access, the opportunities enabled by digital transformation are being harnessed. The paper ends with best practices and policy recommendations to cultivate the ecosystems to support women entrepreneurs and proposes future research directions highlighting digital literacy and cross-cultural studies.